Elements of Ethnotaxonomy in Dhule and Nandurbar Districts (Maharashtra) - Patil*, D.A. (Journal of Ecobiotechnology, 2010)
Dhule and Nandurbar districts of Maharashtra are mainly inhabited by tribals and rural folks. The author’s ethnobotanical and floristic forays in these districts brought out certain elements of ethnotaxonomy like ethnotaxonomic markers, classifications, principles of nomenclature and exomorphic features. The facts gathered indicated that the people in the area are fairly flooded with reckonable elements of ethnotaxonomy. And 22 ethnotaxonomic markers are identified. These are evaluated and discussed pertinently in this paper. —————————————————————————————————– Post Graduate Department of Botany, S.S.V.P.S’s L.K. P.R.Ghogrey Science College, Dhule-424005 (Maharashtra), India *Corresponding author, Email: dapatil_10aug@yahoo.com Cite This Article As: D.A. Patil. 2010. Elements of Ethnotaxonomy in Dhule and Nandurbar Districts (Maharashtra). J. Ecobiotechnol. 2(3): 18-25.